1993
DOI: 10.1159/000284803
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Frontal Lobe Functioning in Schizophrenia and Unipolar Major Depression

Abstract: This study has used neuropsychological tasks – Wisconsin Card Sort (WCST), Trail Making (TMT) A and B, Verbal Fluency, Digit Span – to compare acute and currently off-medication schizophrenics, patients with unipolar nonpsychotic major depression and healthy controls. Both patient groups differed significantly from healthy controls in their neuropsychological performance. Furthermore there was only little (quantitative) difference between schizophrenics and depressed patients in the frontal lobe associated tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
3
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 25 publications
2
39
3
3
Order By: Relevance
“…Subsequent power analyses revealed that 4,000 to 43,000 subjects would have been needed for adequate power to detect a difference between groups. These results are largely in contrast to the existing literature in adults with MDD as assessed by a variety of EF tests (Austin et al, 1992; Degl’ Innocenti et al, 1998; Elliot et al, 1996; Franke et al, 1993; Henderson & Welch, 1988; Merriam et al, 1999; Robertson & Taylor, 1985; Trichard et al, 1995). However, these studies included inpatients or outpatients with psychotic/bipolar types of MDD, which likely depict a more severe depressive episode.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Subsequent power analyses revealed that 4,000 to 43,000 subjects would have been needed for adequate power to detect a difference between groups. These results are largely in contrast to the existing literature in adults with MDD as assessed by a variety of EF tests (Austin et al, 1992; Degl’ Innocenti et al, 1998; Elliot et al, 1996; Franke et al, 1993; Henderson & Welch, 1988; Merriam et al, 1999; Robertson & Taylor, 1985; Trichard et al, 1995). However, these studies included inpatients or outpatients with psychotic/bipolar types of MDD, which likely depict a more severe depressive episode.…”
Section: Discussioncontrasting
confidence: 99%
“…In the adult literature a number of studies provide evidence of executive dysfunction in depressed adults (Channon, 1996; Degl’Innocenti, Argen, & Backman, 1998; Dunkin et al, 2000; Elliott et al, 1996; Fossati, Amar, Raoux, Ergis, & Allilaire, 1999; Franke et al, 1993; M. M. Grant, Thase, & Sweeney, 2001; Henderson & Welch, 1988; Keilip et al, 2001; Merriam, Thase, Haas, Keshavan, & Sweeney, 1999; Oren & Boone, 1991; Robertson & Taylor, 1985; Silberman, Weingartner, & Post, 1983; Trichard et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Franke et al [6] compared neuropsychological functioning in acute patients with schizophrenia or nonpsychotic major depression, who were not currently receiving medication, to healthy controls. They found only small differences in executive functions, verbal fluency, and focused attention between patients with depression or schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggested that subjects with affective disorders perform better overall on neuropsychological tests than subjects with schizophrenia (15). Others found limited differences in performance between the two diagnostic groups (16)(17)(18)(19)(20)(21)(22)(23)(24), especially in subjects with chronic illness or poor outcome (20). Finally, two studies that distinguished between psychotic and nonpsychotic affective disorders reported significant differences between patients with schizophrenia and those with nonpsychotic affective disorders but not between patients with schizophrenia and those with psychotic affective disorders (25,26).…”
mentioning
confidence: 99%